2018
DOI: 10.3233/cbm-170203
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor (GDF-15) concentration combined with Ca125 levels in serum is superior to commonly used cancer biomarkers in differentiation of pancreatic mass

Abstract: In conclusion, GDF-15 is more accurate than Ca19-9 in differentiating pancreatic mass due to chronic pancreatitis from pancreatic adenocarcinoma. Interleukin 17 and 23 cannot be considered as PDAC biomarkers. GDF-15 concentration in serum should be further investigated in order to assess their usefulness in pancreatic adenocarcinoma diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Twelve diagnostic studies [12, 13, 1524], comprising 2380 patients and 4630 paired controls, were included in the diagnostic meta-analysis. The study participants involved included Chinese [12, 13, 16, 20, 21, 23, 24], Australian [17, 19, 22], American [18], Polish [20], and Spanish [15] patients, with sample sizes ranging from 42 to 807. The types of DST covered in these studies included colorectal cancer (CRC) [813], gastrointestinal cancer (GC) [14, 15], pancreatic cancer (PC) [1619], esophageal carcinoma (EC) [21, 22], and liver cancer [23, 24], of which the final diagnoses were all confirmed histologically by surgical operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve diagnostic studies [12, 13, 1524], comprising 2380 patients and 4630 paired controls, were included in the diagnostic meta-analysis. The study participants involved included Chinese [12, 13, 16, 20, 21, 23, 24], Australian [17, 19, 22], American [18], Polish [20], and Spanish [15] patients, with sample sizes ranging from 42 to 807. The types of DST covered in these studies included colorectal cancer (CRC) [813], gastrointestinal cancer (GC) [14, 15], pancreatic cancer (PC) [1619], esophageal carcinoma (EC) [21, 22], and liver cancer [23, 24], of which the final diagnoses were all confirmed histologically by surgical operation.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, GDF-15 levels are substantially increased in various pathological conditions, including inflammation and injury [57]. Notably, experimental and epidemiological evidence has demonstrated that GDF-15 levels are up-regulated in many types of DST, such as colorectal cancer (CRC) [813], gastrointestinal cancer (GC) [14, 15], pancreatic cancer (PC) [1620], esophageal carcinoma (EC) [21, 22], and liver cancer [23, 24]. Recently, GDF-15 has received much attention as a diagnostic and prognostic biomarker in DST.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, another member of the family GDF15 is directly correlated with poor survival in PC patients, and it is proposed as a better marker than CA-125 (66), again raising the atypical functions of this growth factor.…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…As a member of the transforming growth factor (TGF)-β subfamily, growth differentiation factor 15 (GDF-15) is a stress-responsive cytokine associated with various diseases such as cancers [ 1 , 2 , 3 , 4 , 5 ], cardiovascular disorders [ 6 ], mitochondrial disorders [ 7 ], hyperthyroidism [ 8 ], obesity and type 2 diabetes [ 9 ]. GDF-15 mediates food intake, energy consumption, and body weight [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of GDF-15 is maintained at low levels in most tissues [ 21 ] and is increased by p53 activation due to various cellular stressors, such as inflammation, oxidative stress, hypoxia, and oncogene activation [ 22 ]. Serum GDF-15 levels in the patients with chronic pancreatitis were higher, 2248 pg/mL in mean [ 1 ] compared to healthy subjects (416.8 pg/mL [ 23 ], 546 [ 24 ], 639 [ 25 ] in mean). Pancreatic disease compressing the pancreatic duct is considered to increase the GDF-15 level, and thus can result from benign pancreatic diseases including chronic pancreatitis, intraductal papillary mucinous tumor, and serous cystic tumor.…”
Section: Introductionmentioning
confidence: 99%